2005
DOI: 10.1007/s10194-005-0190-1
|View full text |Cite
|
Sign up to set email alerts
|

The comorbidity of migraine and hypertension. A study in a tertiary care headache centre

Abstract: Literature data concerning the comorbidity of migraine and hypertension are conflicting and lacking in consistency [1–4]. This study was designed to evaluate the distribution of hypertension in a sample of migraineurs in comparison with a group of tensiontype headache (TTH) patients. Hypertension prevalence was more elevated in headache sufferers than in the general population. This finding might be due to a Berkson’s bias; in fact individuals seeking medical care often show a high rate of association between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
1
6
2
Order By: Relevance
“…Previously published studies have reported the relationship between migraine and hypertension although sometimes with contradictory results [20][21][22][23][24][25][26][27]. However, these studies had different designs because they were conducted using standardized questionnaires for the general population [20,21,23,24,26,27] or in one specialist center [22,25].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Previously published studies have reported the relationship between migraine and hypertension although sometimes with contradictory results [20][21][22][23][24][25][26][27]. However, these studies had different designs because they were conducted using standardized questionnaires for the general population [20,21,23,24,26,27] or in one specialist center [22,25].…”
Section: Discussionmentioning
confidence: 93%
“…However, these studies had different designs because they were conducted using standardized questionnaires for the general population [20,21,23,24,26,27] or in one specialist center [22,25]. Moreover, in most of the previously published studies, headache patients were identified in the population and investigated for a correlation with the actual levels of BP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertension affects 1 billion people worldwide and is directly responsible for more than 10 million deaths per year, to the extent that it has been declared a global public health crisis by the World Health Organization (49). In previous years, researchers and medical practitioners have made a tremendous effort to study the comorbidities of hypertension (50,51); specifically, heart disease, diabetes, and obesity are the most widely studied comorbidities (52)(53)(54)(55)(56). Therefore, our results are basically consistent with the overall spectrum of chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, hypertension has a large number of comorbidities, which greatly affect hypertension patients' quality of life 5 - 7 . In previous years, researchers and medical practitioners have made a tremendous effort to study the comorbidities of hypertension 8 - 10 . Specifically, heart disease 2 , 11 , diabetes 12 , 13 , and obesity 14 , 15 are the most widely studied comorbidities of hypertension.…”
Section: Introductionmentioning
confidence: 99%